Consider $f:\{1,2,3\} \rightarrow\{a, b, c\}$ given by $f(1)=a, \,f(2)=b$ and $f(3)=c .$ Find $f^{-1}$ and show that $\left(f^{-1}\right)^{-1}=f$.
Function $f :\{1,2,3\} \rightarrow\{ a ,\, b , \,c \}$ is given by $f (1)= a ,\, f (2)= b ,$ and $f (3)= c$
If we define $g:$ $\{a, b, c\} \rightarrow\{1,2,3\}$ as $g(a)=1,\, g(b)=2, \,g(c)=3$
We have
$(f og)(a)=f(g(a))=f(1)=a$
$(f o g)(b)=f(g(b))=f(2)=b$
$(f og)(c)=f(g(c))=f(3)=c$
and
$(\operatorname{gof})(1)=g(f(1))=f(a)=1$
$(\operatorname{gof})(2)=g(f(2))=f(b)=2$
$(\operatorname{gof})(3)=g(f(3))=f(c)=3$
$\therefore$ $gof$ $= I_X$ and $fog =$ $I_Y$, where $X =\{1,2,3\}$ and $Y =\{ a , b , c \}$
Thus, the inverse of $f$ exists and $f-1=g$.
$\therefore f ^{-1}:\{ a , b , c \} \rightarrow\{1,2,3\}$ is given by $f ^{-1}( a )=1,\, f ^{-1}( b )=2,\, f ^{-1}( c )=3$
Let us now find the inverse of $f^{-1}$ i.e., find the inverse of $g$.
If we define $h: \{1,2,3\}$ $\rightarrow\{ a , b , c \}$ as $h (1)= a , \,h (2)= b , \,h (3)= c$
We have
$(\operatorname{goh})(1)=g(h(1))=g(a)=1$
$(\operatorname{goh})(2)=g(h(2))=g(b)=2$
$(\operatorname{goh})(3)=g(h(3))=g(c)=3$
and
$(\operatorname{hog})(a)=h(g(a))=h(1)=a$
$(\operatorname{hog})(b)=h(g(b))=h(2)=b$
$(\operatorname{hog})(c)=h(g(c))=h(3)=c$
$\therefore \operatorname{goh}=$ $I_X$ and $hog$ $=$ $I_Y$, where $X=\{1,2,3\}$ and $Y=\{a, b, c\}$
Thus, the inverse of $g$ exists and $g ^{-1}= h \Rightarrow\left( f ^{-1}\right)^{-1}= h$
It can be noted that $h = f$.
Hence, $\left(f^{-1}\right)^{-1}=f$
If $f(x) = 3x - 5$, then ${f^{ - 1}}(x)$
Which of the following function is inverse function
Let f : $R \to R$ be defined by $f\left( x \right) = \ln \left( {x + \sqrt {{x^2} + 1} } \right)$ , then number of solutions of $\left| {{f^{ - 1}}\left( x \right)} \right| = {e^{ - \left| x \right|}}$ is
If $f: R \rightarrow R$ be given by $f(x)=\left(3-x^{3}\right)^{\frac{1}{3}},$ then $fof(x)$ is ..........
If $y = f(x) = \frac{{x + 2}}{{x - 1}}$, then $x = $